THE SYMBOLISM OF OBOCHI (DAY) IN IKWERRE TRADITIONAL RELIGION: A LEGACY OF LIVED EXPERIENCE OF PENTECOSTALISM IN CONTEMPORARY NIGERIA (American Journal of Research in Humanities and Social Sciences, 2023)
Man is a cultural being, homo-symbolicus, which in essence means that he is a symbol-using animal. Indeed, his capacity to symbolize is often proposed as a criterion placing him apart from the beasts. Language may be the most important kind of symbolization, but it is not the only one. It has been said that religion may be viewed as a vast symbolic system, as indeed and it is to this possibility that this paper tries to address. Like metaphors, symbols typify or represent or recall something by possession of analogous qualities or by association in fact or thought. But there is no universal meaning that any single motif may be said to symbolize, the Jungian notion of archetypes notwithstanding. Symbols and what they signify are above all culturally constructed and culturally bound. One culture’s symbolic analogy is another culture’s puzzle. The work x-rays the Symbolism of Obochi (Day) in Ikwerre Traditional Religion: A Legacy of Lived Experience of Pentecostalism in Contemporary Nigeria. Ikwerre is located at North Eastern Niger Delta of Nigeria. The majority of the African people including Ikwerre believe in African traditional religion (ATR). This ATR is the all-pervasive determinant of the people’s life and culture. It is part and parcel of the cultural heritage of the people and determines the spontaneous and subconscious reactions of the people and their interpretation of reality. The methodology adopted in this work is hermeneutic and descriptive phenomenological method of investigation. Therefore, the work recommends that the dominant culture should not swallow up the minor cultures, therefore, the minor culture should be allowed to stay.